Privacy-Preserving Data Mining Methods Metrics and Applications in Healthcare Informatics - Shukla Abhay; Chaurasia Shubham; Pandey Gaurav; Kumar Shukla Sanjeev; Singh Parihar Subhash; P B Edwin Prabhakar (ITM Web of Conferences)
Their fields have a profound interest in PPDM as a technical progress in health informatics, balancing the need to extract valuable information for clinical decisions while preserving sensitive data. Classic federated learning (FL) models have various limitations like intensive computational loads and privacy leakage risks. In this paper, we propose an optimized lightweight federated framework that increases computational efficiency without compromising privacy properties. Furthermore, an adaptive noise optimiz… (Note: This is the previous version condensed to lower the response time but are still ok.) In addition, because of security, a hybrid blockchain integrated data mining approach is created to implemented secure verifiable transaction with reduced the overhead in multiple health care institutions. In addition, a scalable privacy-preserving deep learning model is proposed for big patient datasets. To address this challenge, this work develops a full-fledged privacy-preserving AI benchmarking framework for the harmonized evaluation of sensitive data across different healthcare data sets. Lastly, the suggested framework helps to identify alignment with global privacy regulations including HIPAA and GDPR, thus enabling ethical compliance and encouraging responsible AI-led healthcare innovations. Our study paves the way for a secure, scalable, and efficient privacy-preserving data mining in the healthcare informatics ecosystem.